Knowledge and attitudes of young women regarding BSE at state Junior High School 21 Palu, South Palu District, Palu City, Central Sulawesi - Purwiningsih, Sri; Arni, Fitri; Parmi, Parmi; Susianawati, Desak E; Kantohe, Imelda; Taurisa, Almaida (Science Midwifery, 2024)
The incidence of cases in Palu City as the Municipality of Central Sulawesi is with a rate of 11 new cases per year 2022, 4 old cases per year 2022, and 4 cases of deaths per year 2022. This research aims to find out how young people's knowledge and attitudes are. Putri about SADARI State Junior High School 21 Palu. The type of research is descriptive. This research uses secondary data and primary data and is analyzed using univariate analysis. The population taken in this research was the total number of 2nd and 3rd grade female students at SMPN 21 Palu as many as 30 female students. The sample in this study was the entire population, namely 30 female students. The results of the research show that of the 30 respondents in this study, there were more who had sufficient knowledge, namely 53.3% and had a fair attitude, namely 73.3%, compared to respondents who had good knowledge, which amounted to 6.6% and the remaining respondents who had less knowledge, amounted to 40%. and 26.6% of respondents had a negative attitude towards BSE. The conclusion of this research is that more female students are knowledgeable and have adequate attitudes about BSE. The suggestion in this research is that it is hoped that State 21 Palu Junior High School will further intensify the BSE movement through outreach activities regarding early examination.